2011
DOI: 10.1111/j.1464-5491.2010.03205.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of gestational diabetes mellitus in Chinese women from 1999 to 2008

Abstract: The prevalence of gestational diabetes mellitus has markedly been increasing in a universally screened urban Chinese female population and has become an important public health problem in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 25 publications
6
165
1
Order By: Relevance
“…Given the rise in the incidence of GDM over the past decade in China2, research to identify modifiable determinants of glucose intolerance has become a public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rise in the incidence of GDM over the past decade in China2, research to identify modifiable determinants of glucose intolerance has become a public health priority.…”
Section: Introductionmentioning
confidence: 99%
“…Coinciding with the rapid economic development, the Chinese population has been experiencing a rapid lifestyle change, tending toward a more sedentary and high-energy/ high-fat diet (27). These changes have resulted in marked increases of both overweight (from 20.0% in 1992 to 29.9% in 2002 in Chinese aged 18 years) (28,29) and GDM (from 2.4% in 1999 to 8.2% in 2012 in urban Chinese women aged 20 years) (30). As overweight and GDM are both important risk factors for diabetes, the control of overweight among women with prior GDM could largely reduce and delay the development of diabetes.…”
Section: Original Article Obesity Epidemiology/geneticsmentioning
confidence: 99%
“…All pregnant women at 26-30 gestational weeks participated in a 1-h 50-g glucose screening test (GCT). Women who had a glucose reading 7.8 mmol/l were invited to undergo a 2-h 75-g oral glucose tolerance test (OGTT) at the Tianjin Women and Children's Health Center (7). GDM is defined using the using the World Health Organization (WHO)'s criteria (8).…”
Section: Tianjin Gdm Screening Projectmentioning
confidence: 99%
“…2 In the 1990s, the prevalence of GDM in Hong Kong was approximately 14.2%. 3 Studies in China and the United States show that the incidence of GDM has been increasing in recent years, 4,5 thus increasing the risk of complications for both mother and child during pregnancy, childbirth, and beyond. 6 Notably, it is reported that high first-trimester glucose levels are associated with an increased risk of a diagnosis of GDM later in pregnancy and adverse pregnancy outcome.…”
Section: Introductionmentioning
confidence: 99%